Determining Image Opacity in Broiler Respiratory Radiographic Using ImageJ and Ansel Adam’s Zone System (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
The diagnosis of diseases of the respiratory, lung, and air sacs generally uses radiographic images by radiologists. Therefore, the results are very subjective, causing differences in the interpretation and diagnosis among different radiologists. A radiographic image reading needs to be made in the form of a simple, fast, and accurate algorithm. The study aimed to reduce subjectivity and be easily carried out by radiology medical personnel, especially veterinarians. This study carried out density measurements by image processing using ImageJ software on 14 radiographic images of broiler chickens. Furthermore, the density value is associated with the Ansel Adam's - grayscale system to determine the opacity of respiratory tract tissues/organs, which were previously inhaled by one of them with chitosan-iopamidol nanoparticles using a nebulizer. The results of density measurements for the category of opacity in radiographic images are that seven spot areas lead brighter (radiopaque) only in chickens that are inhaled mist maker of chitosan-iopamidol nanoparticles. Then the determination of the value range is obtained average value on two ventrodorsal radiographic images, which are inhaled by mist maker of chitosan-iopamidol nanoparticles and chitosan nanoparticle compressor. The conclusion of this study was only in chickens that were infested with mist maker chitosan-iopamidol, whose radiographic image had a radiopaque spot and middle-value area.
Keywords: Ansel Adam’s; ImageJ; radiology; radioopaque; subjectivity